Primary Cell-Derived Intestinal Models: Recapitulating Physiology. Issue 7 (July 2019) - Dutton, Johanna S.; Hinman, Samuel S.; Kim, Raehyun; Wang, Yuli; Allbritton, Nancy L.
Abstract : The development of physiologically relevant intestinal models fueled by breakthroughs in primary cell-culture methods has enabled successful recapitulation of key features of intestinal physiology. These advances, paired with engineering methods, for example incorporating chemical gradients or physical forces across the tissues, have yielded ever more sophisticated systems that enhance our understanding of the impact of the host microbiome on human physiology as well as on the genesis of intestinal diseases such as inflammatory bowel disease and colon cancer. In this review we highlight recent advances in the development and usage of primary cell-derived intestinal models incorporating monolayers, organoids, microengineered platforms, and macrostructured systems, and discuss the expected directions of the field. Highlights: Breakthroughs in primary cell culture have paved the way for the development of in vitro intestinal models that closely mimic in vivo physiology. Organoids are the most widely used system for modeling the intestinal epithelium using primary cells, and have recently been used to study extracellular matrix–cell interactions, microbiota interfaces, and population screens. Monolayer culture formats provide a simple and robust approach to generate in vitro intestinal epithelium, providing access to both luminal and basal cell sides, and incorporating crucial attributes required for screening applications. Microengineered intestinal epithelial models can recapitulate key aspects of intestinal physiology, including microarchitecture, flow, and peristalsis, that are difficult to implement in conventional culture systems, offering more accurate intestine models for preclinical studies.